2015
DOI: 10.1038/srep09589
|View full text |Cite
|
Sign up to set email alerts
|

Fructose decreases physical activity and increases body fat without affecting hippocampal neurogenesis and learning relative to an isocaloric glucose diet

Abstract: Recent evidence suggests that fructose consumption is associated with weight gain, fat deposition and impaired cognitive function. However it is unclear whether the detrimental effects are caused by fructose itself or by the concurrent increase in overall energy intake. In the present study we examine the impact of a fructose diet relative to an isocaloric glucose diet in the absence of overfeeding, using a mouse model that mimics fructose intake in the top percentile of the USA population (18% energy). Follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 60 publications
2
24
1
3
Order By: Relevance
“…To investigate the metabolic programming of the post‐weaning diet on later life health, the fructose and glucose diets were replaced by an HF diet after 3 weeks. It was recently shown that continuing on a fructose rich diet (compared to a glucose rich diet) affects BW gain adversely: young male mice on a fructose diet (18 en%) gained more BW than on a glucose diet (18 en%), although this difference only appeared after 4 weeks . Here, FM in females had a tendency to be higher in the FRU group at the end of the intervention, suggesting FM could be negatively affected if the diet had been continued.…”
Section: Discussionmentioning
confidence: 87%
“…To investigate the metabolic programming of the post‐weaning diet on later life health, the fructose and glucose diets were replaced by an HF diet after 3 weeks. It was recently shown that continuing on a fructose rich diet (compared to a glucose rich diet) affects BW gain adversely: young male mice on a fructose diet (18 en%) gained more BW than on a glucose diet (18 en%), although this difference only appeared after 4 weeks . Here, FM in females had a tendency to be higher in the FRU group at the end of the intervention, suggesting FM could be negatively affected if the diet had been continued.…”
Section: Discussionmentioning
confidence: 87%
“…Studies on fructose intake have reported that consumption of fructose is associated with weight gain and may also contribute to the development of obesity with IR . In addition, Rendeiro et al showed a significant increase in the liver and mass, as well as the body weight of the fructose‐receiving group without any difference in calories between the 2 groups given glucose and fructose. The authors explained the results could be because of the decrease in physical activity in the fructose group.…”
Section: Discussionmentioning
confidence: 99%
“…It can be expected that similar problems will occur in gut microbes exposed to glyphosate, as well as human cells, and this may explain the increased levels of methylglyoxal observed in association with diabetes [74]. A study comparing rats fed a high-fructose compared to a high-glucose diet revealed that those rats fed fructose experienced a significant increase in body weight, liver mass and fat mass compared to the glucosefed rats [75]. This was accompanied by a reduction in physical activity, although the total number of calories consumed remained equivalent.…”
Section: Glyoxal Methylglyoxal and Glyoxylatementioning
confidence: 99%